Expression of hormone receptors in low-grade adenosquamous carcinoma of the breast: A case report. Issue 46 (November 2017) - Wu, Hai-Bo; Zhang, An-Li; Wang, Wei; Li, Heng
Abstract: Rationale: Low-grade adenosquamous carcinoma (LGASC) is a rare subtype of metaplastic breast carcinoma which is generally recognized as a characteristic subgroup of triple-negative breast cancers previously. However, in this study, we reported for the first time a case of LGASC with hormone receptors expression. Patient concerns: Pathological analysis of breast tumor specimen obtained by a 42-year-old female patient was performed. Morphologically, it composed of glandular structures with scattered squamous differentiation accompanied by haphazard arrangement of spindle cell stroma. Immunohistochemically, all myoepithelial and squamous differentiation markers showed typical LGASC positive or negative staining pattern. Interestingly, we found that normally aberrant hormone receptors were reactivated in this case. To our knowledge, this is the first report of a hormone receptor-positive LGASC. Apart from this, in the extended resection sample, we found scattered squamous metaplasia and florid adenosquamous proliferation (ASP). Meanwhile, it was positive for CD44 variant isoforms (CD44v), which is a breast cancer stem cell (CSC) marker, and expressed in LGASC, squamous metaplasia, and ASP. Diagnosis: LGASC with hormone receptors expression. Interventions: The breast-extended local excision and axillary lymph node dissection were performed. Outcomes: The patient was free of local recurrence and distant metastasis 6 months after surgical resection. Lessons: We herein report the first case of LGASC with immunoreactivity for hormone receptors, expanding its profile of immunophenotypes. CD44v may play an important role in the transition of LGASC precursor lesions into malignant processes, which may serve as a therapeutic target in LGASC.